1995
DOI: 10.1002/polb.1995.090331409
|View full text |Cite
|
Sign up to set email alerts
|

Rodlike/flexible polyimide composite films prepared from soluble poly(amic diethyl ester) precursors: Miscibility, structure, and properties

Abstract: Homogeneous precursor/precursor solutions with various compositions were obtained with appreciably high solid contents in N‐methyl‐2‐pyrrolidone from soluble poly(amic diethyl ester) precursors of rodlike poly(p‐phenylene biphenyltetracarboximide) (BPDA‐PDA) and flexible poly(4,4′‐oxydiphenylene biphenyltetracarboximide) (BPDA‐ODA), which are hydrolytically more stable as well as more soluble than the corresponding poly(amic acid)s being equilibrated with the constituent monomers. Both optical microscopic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…For aromatic polyimides, their mechanical properties are also known to vary with the history of precursor origins used in the film formation [28][29][30] . However, the mechanical properties of PMDA-ODA PI are insensitive to its precursor origins, PAA and PAE precursors: 3.0 GPa Young's modulus and ca.…”
Section: Adhesion Propertiesmentioning
confidence: 99%
“…For aromatic polyimides, their mechanical properties are also known to vary with the history of precursor origins used in the film formation [28][29][30] . However, the mechanical properties of PMDA-ODA PI are insensitive to its precursor origins, PAA and PAE precursors: 3.0 GPa Young's modulus and ca.…”
Section: Adhesion Propertiesmentioning
confidence: 99%
“…[1][2][3][4] Since polyimide (PI) is, however, originated from organic materials, there exists a limit for far higher performance applications in which inorganic materials are used.…”
Section: Introductionmentioning
confidence: 99%
“…[6±11] Although optically transparent polyimide composite films were successfully prepared using soluble precursors, poly(amic acid) and/or poly(amic dialkyl ester), which are well dissolved in common weak base solvents, careful studies showed that the resulting polyimide composite films were phase segregated on a scale of several nanometers, meaning a nanocomposite rather than a molecular composite, because rigid rod-like polyimides have inherently high tendency to intermolecular chain packing and preferential in-plane molecular orientation. [9,11] In particular, these previous reports focused on the physical and structural analysis in order to study the formation of molecular composite. However, the in-plane and outof-plane optical and dielectric properties have not been investigated yet, even though this is one of major causes to make the polyimide molecular composite because the dielectric constant of the packaging or inter-dielectric layers has a huge influence on the delay of signal propagation and crosstalk between other signal lines.…”
mentioning
confidence: 99%
“…This nonlinear dependence of refractive index on the composition suggests that the mixing between BPDA-PDA PI and BPDA-ODA PI is not on a molecular level but several nanometers scale. [9] Kim et al In order to investigate the relationship between this optical anisotropy and nanostructure of the composite films, high resolution x-ray diffraction patterns were measured for both in-plane and out-of-plane direction. As shown in Figure 7, the measurement was particularly focused on the characteristic angle of 11 corresponded to the (004) in-plane orientation of BPDA-PDA PI and 18.7 ± 0.2 corresponded to one of the out-of-plane amorphous halos of BPDA-ODA PI.…”
mentioning
confidence: 99%
See 1 more Smart Citation